2019
DOI: 10.1002/ejoc.201900335
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Electrophilic Amination of Benzoxazoles via Magnesation

Abstract: One‐pot synthesis of 2‐aminobenzoxazoles through copper‐catalyzed electrophilic amination of benzoxazoles with O‐benzoyl hydroxylamines is described. The direct magnesation of benzoxazoles with the readily available iPrMgCl generated benzoxazolylmagnesium reagents in situ and these reagents were treated with electrophilic amines in the presence of 10 mol‐% Cu(OAc)2 and ZnCl2 under mild reaction conditions. A variety of 2‐aminobenzoxazoles were obtained in good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…A copper-catalyzed amination of benzoxazole was disclosed by Lee et al [34] Here, 2-aminobenzoxazole was attained through the reaction of benzoxazole and o-benzoyl hydroxylamine at À 10 °C. The reaction underwent smoothly in the presence of 10 mol % of Cu(OAc) 2 and 50 mol % of ZnCl 2 in THF as the solvent.…”
Section: Copper-catalyzed Aminationmentioning
confidence: 99%
See 1 more Smart Citation
“…A copper-catalyzed amination of benzoxazole was disclosed by Lee et al [34] Here, 2-aminobenzoxazole was attained through the reaction of benzoxazole and o-benzoyl hydroxylamine at À 10 °C. The reaction underwent smoothly in the presence of 10 mol % of Cu(OAc) 2 and 50 mol % of ZnCl 2 in THF as the solvent.…”
Section: Copper-catalyzed Aminationmentioning
confidence: 99%
“…A copper‐catalyzed amination of benzoxazole was disclosed by Lee et al [34] . Here, 2‐aminobenzoxazole was attained through the reaction of benzoxazole and o ‐benzoyl hydroxylamine at −10 °C.…”
Section: Classificationmentioning
confidence: 99%
“…The same year, Lee et al reported the electrophilic amination of heteroaryl Grignard reagents . The latter were obtained by metalation using i PrMgCl and then were directly involved in the electrophilic amination with O -benzoyl-hydroxylamine, in the presence of ZnCl 2 (50 mol %) and Cu­(OAc) 2 (10 mol %) in THF at rt.…”
Section: Umpolung Couplingsmentioning
confidence: 99%
“…68 The reaction proceeds in acetonitrile at 40 °C in the presence of CuBr 2 (5 mol %) as a catalyst, with 1.3 equiv of LiCl as additive, in the absence of a The same year, Lee et al reported the electrophilic amination of heteroaryl Grignard reagents. 69 The latter were obtained by metalation using iPrMgCl and then were directly involved in the electrophilic amination with O-benzoylhydroxylamine, in the presence of ZnCl 2 (50 mol %) and Cu(OAc) 2 (10 mol %) in THF at rt. This procedure does not require the stepwise formation of the organozinc reagent and could be applied to various heterocycles and O-benzoylhydroxylamines (Scheme 54).…”
Section: 24mentioning
confidence: 99%
“…Several methods for synthesis of 2-aminobenzoxazoles have been reported (Scheme ). , However, most of these methods suffer from specific drawbacks. The most published protocol comprises the cyclization of 2-aminophenols using BrCN as a cyanating agent, , , but this BrCN reagent is highly toxic.…”
Section: Introductionmentioning
confidence: 99%